(untitled) (Journal of Asian Development Studies, 2025)
The present study investigates the effect of export diversification in non-oil products (NOED) on the economic stability in Saudi Arabia and detects the key drivers of NOED. Using the Johansen cointegration technique on time-series data from 1990 to 2024, the findings reveal that NOED, along with foreign direct investment and gross capital formation, positively influence long-run economic growth. However, NOED exhibits no significant correlation with GDP per capita in the short term. The outcomes also indicate that the rule of law and the labour force are positive long run drivers of NOED, while population has a negative association with it. In the short run, population growth positively affects NOED, whereas the labour force and trade openness negatively affect it. Overall, these results align with Saudi Vision 2030, which emphasises expanding non-oil exports, investing in human capital, and reforming institutions to achieve a diversified, resilient, and stable economy.